Association of Stroke Subtype With Hemorrhagic Transformation Mediated by Thrombectomy Pass: Data From the ANGEL-ACT Registry. Issue 6 (31st March 2022) - Tong, Xu; Burgin, W. Scott; Ren, Zeguang; Jia, Baixue; Zhang, Xuelei; Huo, Xiaochuan; Luo, Gang; Wang, Anxin; Zhang, Yijun; Ma, Ning; Gao, Feng; Song, Ligang; et al.
Abstract : Background: The role of stroke etiology subtype in patients with acute large vessel occlusion on the occurrence of hemorrhagic transformation (HT) after endovascular treatment is poorly studied, and which factors mediate their relationship remains largely unknown. We utilized nationwide registry data to explore the association of stroke subtype (cardioembolism versus large artery atherosclerosis) with HT and to identify the possible mediators. Methods: A total of 1015 subjects were selected from the ANGEL-ACT registry (Endovascular Treatment Key Technique and Emergency Work Flow Improvement of Acute Ischemic Stroke)—a prospective consecutive cohort of acute large vessel occlusion patients undergoing endovascular treatment at 111 hospitals in China between November 2017 and March 2019—and divided into large artery atherosclerosis (n=538) and cardioembolism (n=477) according to the Trial of ORG 10172 in Acute Stroke Treatment criteria. The types of HT included any intracerebral hemorrhage (ICH), parenchymal hematoma, and symptomatic ICH within 24 hours after endovascular treatment. The association between stroke subtype and HT was analyzed using a logistic regression model. Mediation analysis was done to assess how much of the effect of stroke subtype on HT was mediated through the identified mediators. Results: Stroke subtype (cardioembolism versus large artery atherosclerosis) was associated with increased risk of any ICH (29.8% versus 16.5%; odds ratio, 2.03 [95% CI, 1.22–3.36]), parenchymal hematoma (14.3% versus 5.4%; odds ratio, 2.90 [95% CI, 1.38–6.13]), and symptomatic ICH (9.9% versus 4.7%; odds ratio, 2.59 [95% CI, 1.09–6.16]) after adjustment for potential confounders. The more thrombectomy passes in cardioembolism patients had a significant mediation effect on the association of stroke subtype with increased risk of HT (any ICH, 15.9%; parenchymal hematoma, 13.4%; symptomatic ICH, 14.2%, respectively). Conclusions: Stroke subtype is an independent risk factor for HT within 24 hours following endovascular treatment among acute large vessel occlusion patients. Mediation analyses propose that stroke subtype contributes to HT partly through thrombectomy pass, suggesting a possible pathomechanistic link. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03370939.